Comparative Analysis of L-Fucose Utilization and Its Impact on Growth and Survival of Campylobacter Isolates - Middendorf, Pjotr S.; Jacobs-Reitsma, Wilma F.; Zomer, Aldert L.; den Besten, Heidy M. W.; Abee, Tjakko (Frontiers in Microbiology, 2022)
Campylobacter jejuni and Campylobacter coli were previously considered asaccharolytic, but are now known to possess specific saccharides metabolization pathways, including L-fucose. To investigate the influence of the L-fucose utilization cluster on Campylobacter growth, survival and metabolism, we performed comparative genotyping and phenotyping of the C. jejuni reference isolate NCTC11168 (human isolate), C. jejuni Ca1352 (chicken meat isolate), C. jejuni Ca2426 (sheep manure isolate), and C. coli Ca0121 (pig manure isolate), that all possess the L-fucose utilization cluster. All isolates showed enhanced survival and prolonged spiral cell morphology in aging cultures up to day seven in L-fucose-enriched MEMα medium (MEMαF) compared to MEMα. HPLC analysis indicated L-fucose utilization linked to acetate, lactate, pyruvate and succinate production, confirming the activation of the L-fucose pathway in these isolates and its impact on general metabolism. Highest consumption of L-fucose by C. coli Ca0121, is conceivably linked to its enhanced growth performance up to day 7, reaching 9.3 log CFU/ml compared to approximately 8.3 log CFU/ml for the C. jejuni isolates. Genetic analysis of the respective L-fucose clusters revealed several differences, including a 1 bp deletion in the Cj0489 gene of C. jejuni NCTC11168, causing a frameshift in this isolate resulting in two separate genes, Cj0489 and Cj0490, while no apparent phenotype could be linked to the presumed frameshift in the NCTC11168 isolate. Additionally, we found that the L-fucose cluster of C. coli Ca0121 was most distant from C. jejuni NCTC11168, but confirmation of links to L-fucose metabolism associated phenotypic traits in C. coli versus C. jejuni isolates requires further studies.